Coaching for high performance - Payne, Vivette (American Management Association, 2007)
Coach employees to ensure maximum performance, motivation and retention. Following a seven-step coaching process, Coaching for High Performance gives managers the tools to help their people excel at their jobs and meet competitive challenges with confidence. This book teaches managers how to communicate performance expectations, assess employee skill levels, establish the purpose of coaching, and agree on a coaching contract. Managers will learn the critical skills needed to conduct coaching conversations, adapt one's coaching style to fit changing situations, and create a coaching plan. Reade.